Nitrones: not only extraordinary spin traps, but also good nitric oxide sources in vivo - Croitoru Mircea Dumitru; Petkes Hermina Iulia; Fülöp Ibolya; Cotârlan Remus; Şerban Oana Elena; Dogaru Titica Maria; Gâz Florea Şerban Andrei; Tőkés Béla; Majdik Cornelia (Acta Pharmaceutica, 2015)
Free radicals are involved in the development of reperfusion injuries. Using a spin trap, the intensity of such lesions can be reduced. Nitrones (effective in vivo spin traps) were tried in this work as in vivo nitric oxide donors. Nitrite and nitrate concentration values (rabbit blood) were used as biomarkers of nitric oxide production. Most nitrones did not increase plasma concentrations of nitrite and nitrate; on the contrary, reduced plasma concentrations of these indicators were noted. However, glyoxal isopropyldinitrone, in a dose of 50 mg kg-1, was highly effective in increasing nitric oxide production. At the same time, nitrones do not react with hepatic homogenates, proving that the release of nitric oxide takes place in the tissues and is not related to hepatic metabolism. Before using nitrones in vivo, they were tested in vitro for the ability to release nitric oxide following a reaction with the hydroxyl radical.